(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the revealing the concept of "safe mahalla". The author also explains in the article some aspects of demographic, socio-economic, geographical as well as social and spiritual factors that affect the understanding and scientific study of the concept of "safe mahalla".